2022
DOI: 10.1155/2022/4775645
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin Upregulates Mitochondrial Thioredoxin of Schwann Cells to Improve Diabetic Peripheral Neuropathy Indicated by 4D Label-Free Quantitative Proteomics

Abstract: Diabetic peripheral neuropathy (DPN) is a diabetic complication characterized by demyelination. The pathogenesis of DPN has not been fully elucidated, thus lacking therapies. In the current study, we aimed to confirm whether paeoniflorin (PF) could improve DPN by upregulating mitochondrial thioredoxin (Trx2) based on 4D Label-free proteomic experiments of Schwann cells (SCs) mitochondria. Firstly, PF increased the expression of mitochondrial processing peptidase α (Pmpca) and small ubiquitin-related modifier 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Therefore, reducing the content of ROS to block the ROS-activated apoptotic pathway may be a new therapeutic target for diabetic autonomic neuropathy. 21 Our data showed that the content of ROS in the SG of DM rats was significantly increased, whereas lncRNA-UC.360+ shRNA treatment could reduce the ROS overproduction in DM rats, suggesting the beneficial effect of lncRNA-UC.360+ shRNA on reducing the ROS produced at high glucose in diabetes.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Therefore, reducing the content of ROS to block the ROS-activated apoptotic pathway may be a new therapeutic target for diabetic autonomic neuropathy. 21 Our data showed that the content of ROS in the SG of DM rats was significantly increased, whereas lncRNA-UC.360+ shRNA treatment could reduce the ROS overproduction in DM rats, suggesting the beneficial effect of lncRNA-UC.360+ shRNA on reducing the ROS produced at high glucose in diabetes.…”
Section: Discussionmentioning
confidence: 55%
“…High glucose can prompt cells to produce excess ROS, which in turn regulates the activation of protein kinase C, MAPK, and various cytokines and transcription factors, resulting in enhanced expression of cell-injury molecules, which ultimately leads to sympathetic neuropathy in diabetes. Therefore, reducing the content of ROS to block the ROS-activated apoptotic pathway may be a new therapeutic target for diabetic autonomic neuropathy . Our data showed that the content of ROS in the SG of DM rats was significantly increased, whereas lncRNA-UC.360+ shRNA treatment could reduce the ROS overproduction in DM rats, suggesting the beneficial effect of lncRNA-UC.360+ shRNA on reducing the ROS produced at high glucose in diabetes.…”
Section: Discussionmentioning
confidence: 64%
“…Paeoniforin also has an action at the level of increasing the expression of mitochondrial processing peptidase α (PMPCA) and small ubiquitin 1 (Sumo1) which are responsible for increasing mitochondrial Trx2 (thioredoxin 2) protein processing and increasing Trx2 levels, TrxR2, and Prx3 in the sciatic nerve of rats with diabetic neuropathy, a severe consequence of diabetes mellitus, thereby reducing demyelination as well as improving mechanical pain threshold, thermal pain threshold, motor nerve conduction velocity (MNCV), and sensory nerve conduction velocity (SNCV). Overall, these results suggest that paeoniforin could provide protection for the diabetic neuropathy (ND) condition by regulating Trx2 [98]. Paeoniforin is, therefore, a natural glycoside with antihyperglycemic efect.…”
Section: Catalpolmentioning
confidence: 79%
“…EVs were isolated from tick hemolymph by differential centrifugation, as previously described [ 48 ]. The hemolymph was mixed with an equal volume of PBS and centrifuged at 500 × g for 10 min at 4 °C to remove any contaminating cells.…”
Section: Methodsmentioning
confidence: 99%
“…The 4D label-free proteomic protocol used here was described previously in [ 48 , 49 ]. Briefly, SDT (4% SDS, 100 mM Tris–HCl, 1 mM DTT, pH 7.6) buffer was used for sample lysis and protein extraction.…”
Section: Methodsmentioning
confidence: 99%